2017
DOI: 10.19082/ah207
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of Inbound and Outbound Medical Tourism Companies: A Review Article

Abstract: Medical tourism refers to travel abroad to obtain medical services. Medical tourism plays an important role in the future of medical and tourism industries throughout the world, due to the development of healthcare technologies, facilities, and some global changes. Right now, medical tourists or international patients use medical tourism agents and facilitators to find reliable providers and have trouble-free travel arrangements. Medical tourism facilitators can positively influence patients' health-seeking be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In this process, sustainable medical tourism facilitators present several medical options to patients from introducing medical treatments and service and helping with choosing a country or city for treatment; it is also important to take advantage of a facilitator or an intermediary to advance technologies available in each particular medical destination [44]. Several researchers highlighted the importance of the internet in facilitators' businesses and suggested that the internet functions as a 'global marketing platform', where individuals seeking private health care discover facilitators and hospitals beyond their country of residence [47][48][49]. A large number of patients who are seeking private health care in foreign countries contact facilitators to obtain information on treatment abroad for health care [50].…”
Section: Discussionmentioning
confidence: 99%
“…In this process, sustainable medical tourism facilitators present several medical options to patients from introducing medical treatments and service and helping with choosing a country or city for treatment; it is also important to take advantage of a facilitator or an intermediary to advance technologies available in each particular medical destination [44]. Several researchers highlighted the importance of the internet in facilitators' businesses and suggested that the internet functions as a 'global marketing platform', where individuals seeking private health care discover facilitators and hospitals beyond their country of residence [47][48][49]. A large number of patients who are seeking private health care in foreign countries contact facilitators to obtain information on treatment abroad for health care [50].…”
Section: Discussionmentioning
confidence: 99%